Dynamics of Personalization of Political Parties in the Recruitment of Prospective Candidates for Mayor of Solo 2020 (Case Study of the Indonesian Democratic Party of Struggle (PDI-P)) - Mochamad Atami Ridwan; Fatkhuri (Indonesian Scientific Publication, 2023)
This study aims to explain the dynamics that occur in the recruitment process for candidates for Mayor of Solo in the 2020 simultaneous local elections. These dynamics are influenced by personalized action within the party characterized by the dominance of the general chairperson and the weakness of the party organization. The method used in this research is descriptive qualitative using primary and secondary data including interviews, documentation, and literature study. The results obtained from this study indicate that there are problems in the recruitment function for candidates for Mayor of Solo, including intervention from the Party Chairperson as a result of his strong domination in political parties so that the party structure at the local level, namely the PDI-P DPC Surakarta City cannot implementing a bottom-up scheme by nominating candidates based on the election results. The weakness of party institutions can also be seen in party regulations regarding the recruitment of regional heads which are not implemented properly, not reflected in the principles of democracy within the party, the lack of independence of the party structure at the local level, to the pragmatism of the party by nominating a solo mayoral candidate based on the candidate's social background. is the son of the son of President Joko Widodo who is currently in office.